(untitled) - Ginsberg, Leon H (Chicago, 1998)
Includes bibliographical references (p. 197-203) and index; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: United States -- Social policy; Public welfare -- United States; Welfare state; Conservatism -- United States; Phúc lợi xã hội -- Hoa Kỳ; Chính sách phúc lợi; Chủ nghĩa bảo thủ -- Hoa Kỳ